Dirasah Tahliliyah 'An Ahammiyah Ma'rifah al-Tashrif fi Fahmi al-Lughah al-Arabiyah - Ritonga, Mahyudin; Alrasi, Fitri; Bambang, Bambang (Institut Agama Islam Negeri (IAIN) Curup, 2018)
Understanding of tashrif is one part in Arabic, everybody cannot understand a vocabulary or even an Arabic sentence without if not understanding tashrif. So, write this article to analyze the urgency of tashrif in Arabic. The method used in this research is literature study, which is reading every reference related to research focus. The research findings show that tashrif is important in understanding mufradat, because with one word tashrif can be formed some other mufradat. Likewise tashrif important in understanding the sentence, because in the sentence sentence there are two words or more the same origin he said but it has different meaning. In addition, the urgency of tashrif can also be seen in the sense of Arabic texts, because one word in Arabic can be shaped into several different words.